A rare case of osteoblastoma associated to aneurysmal bone cyst of the spine. Case report. (2nd January 2016) - Pavanello, Marco; Melloni, Ilaria; Fiaschi, Pietro; Consales, Alessandro; Piatelli, Gianluca; Ravegnani, Marcello; Nozza, Paolo; Gandolfo, Carlo; Cama, Armando
Abstract : Osteoblastoma is a rare bone tumour. It is occasionally associated with an aneurysmal bone cyst (ABC). Several treatment strategies can be adopted. We report a challenging case of an osteoblastoma associated with ABC of the lumbar spine in a 2-year-old boy. The pathogenesis and the critical management of the disease are discussed.